Evaluation of extraocular muscles in patients with thyroid associated ophthalmopathy using apparent diffusion coefficient measured by magnetic resonance imaging before and after radiation therapy. (September 2022) - Yu, Wu; Zheng, Lao; Shuo, Zhang; Xingtong, Liu; Mengda, Jiang; Lin, Zhang; Ziyang, Shao; Huifang, Zhou
Background: Thyroid-associated ophthalmopathy (TAO) is an autoimmune orbital disease characterized by edema of extraocular muscles (EOMs). Purpose: To characterize the inflammation of EOMs in patients with TAO before and after radiation therapy using apparent diffusion coefficient (ADC) and to analyze the correlation between ADC and clinical activity of TAO. Material and Methods: The ADCs of superior rectus (SR), inferior rectus (IR), medial rectus (MR), and lateral rectus (LR) muscles were measured in 52 eyes of 26 patients with TAO before and three months after orbital radiation therapy. In addition, 38 eyes of 20 healthy volunteers were included. The clinical activity score (CAS) was evaluated. The ADC maps were reconstructed and measured on the coronal diffusion-weighted imaging (DWI) sequence and calculated in mm 2 /s. Results: The mean ADCs of EOMs before treatment were 1.42 ± 0.23 in SR, 1.37 ± 0.23 in IR, 1.41 ± 0.21 in MR, and 1.28 ± 0.25 in LR. The mean ADCs after treatment were 1.27 ± 0.18, 1.22 ± 0.26, 1.30 ± 0.22, and 1.15 ± 0.21, respectively. The ADCs were significantly decreased after treatment (all P  < 0.001). The ADCs of patients with TAO were significantly higher than those of controls. There was a statistically significant correlation between the mean ADCs and the CAS in each patient with TAO both before and after treatment (before: r = 0.520; P  < 0.001; after: r = 0.625; P  < 0.001). Conclusion: The ADC values of EOMs can be exploited as a quantitative indicator to evaluate the clinical activity and monitor the therapeutic responses of patients with TAO.